Domino Free Flap Transfer Using a Superficial Circumflex Iliac Artery Perforator Flap for the Toe Flap Donor Site. Issue 3 (March 2022) - Fuse, Yuma; Yamamoto, Takumi; Kageyama, Takashi; Sakai, Hayahito; Tsukuura, Reiko; Yoshimatsu, Hidehiko; Yamamoto, Nana
Abstract : Background: Toe-to-hand transfer is a favorable option for finger reconstruction, but donor site healing can be challenging. The superficial circumflex iliac artery perforator (SCIP) flap has yet to be used widely for toe reconstruction. The purpose of this report was to validate the efficacy of the sequential simultaneous free SCIP flap transfer for the toe flap donor site in a consecutive case series. Methods: The medical records of 18 consecutive patients who underwent a simultaneous SCIP flap transfer and a toe-to-hand transplant were reviewed. Free SCIP flap reconstruction was performed in a simultaneous 2-team approach. The SCIP flaps were transferred to various toe flap donor sites: a great toe wraparound flap in 9 cases, a second toe distal phalangeal flap in 4 cases, a great toe osteo-onycho-cutaneous flap in 3 cases, a twisted wraparound flap in 1 case, and a great toe hemipulp flap in 1 case. Results: The size of the SCIP flap ranged from 5 × 3 to 16 × 8 cm. A mean of the total operative time was 229.2 minutes (range, 118–441 minutes; SD, 75.8 minutes). All the SCIP and toe flaps survived completely. Minor wound dehiscence was seen in 2 cases, and the wound healed by conservative treatment. The mean follow-up period was 23.7 months (range, 7–44 months; SD, 9.7 months). No patient had gait dysfunction postoperatively. Conclusions: A sequential SCIP flap transfer was performed simultaneously without additional time, allowing secure soft tissue coverage of the toe flap donor even with avascular tissue such as bone or tendon exposed. The sequential SCIP flap transfer can be a useful option for reconstruction of toe flap donor site, when multiple microsurgeons and microscopes are available.